2008
DOI: 10.1091/mbc.e07-05-0504
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Incorporation of Centromeric Histone CENP-A in Fission Yeast

Abstract: CENP-A is a centromere-specific histone H3 variant that is essential for kinetochore formation. Here, we report that the fission yeast Schizosaccharomyces pombe has at least two distinct CENP-A deposition phases across the cell cycle: S and G2. The S phase deposition requires Ams2 GATA factor, which promotes histone gene activation. In ⌬ams2, CENP-A fails to retain during S, but it reaccumulates onto centromeres via the G2 deposition pathway, which is down-regulated by Hip1, a homologue of HIRA histone chapero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(130 citation statements)
references
References 43 publications
7
121
1
1
Order By: Relevance
“…62 The Δmad2, slp1-mr63, mts3-1, GFP-cnp1, nda3-KM311, cut9-665, slp1-362, his5-303 and lys1-131 are our laboratory stock. 34,42,[49][50][51]63,64 The mutant ubc4-P61S was a generous gift from Dr Hiroaki Seino. 37 Yeast transformations were performed by lithium acetate methods.…”
Section: Methodsmentioning
confidence: 99%
“…62 The Δmad2, slp1-mr63, mts3-1, GFP-cnp1, nda3-KM311, cut9-665, slp1-362, his5-303 and lys1-131 are our laboratory stock. 34,42,[49][50][51]63,64 The mutant ubc4-P61S was a generous gift from Dr Hiroaki Seino. 37 Yeast transformations were performed by lithium acetate methods.…”
Section: Methodsmentioning
confidence: 99%
“…In S. pombe, using a temperature sensitive allele of a fluorescently tagged version of CENP-A Cnp1 , it was shown that CENP-A Cnp1 re-incorporation following a shift to the permissive temperature occurs during two discrete cell cycle phases: early S and, to a lesser extent, G2 phase (Takayama et al 2008). While interpretation of experiments based on such ts-alleles is difficult, they suggest that CENP-A is assembled primarily upon mitotic exit (that in fission yeast is immediately followed by S phase), consistent with observations in human cells.…”
Section: Conservation and Differences Of Temporal Control Among Eukarmentioning
confidence: 99%
“…Limiting CENP-A assembly to outside S phase can therefore help restrict it to the centromere. In fission yeast, CENP-A assembly occurs in early S phase (Takayama et al 2008). However, CENP-A gene synthesis precedes bulk H3 synthesis and centromeres are early replicating, potentially facilitating centromere specific deposition of CENP-A even in a system where assembly is overlapping with S phase (Castillo et al 2007).…”
Section: Importance Of Cell Cycle Control Of Cenp-a Assemblymentioning
confidence: 99%
“…Two independent investigations have led to somewhat different conclusions for CENP-A/ Cnp1 deposition in fission yeast. One suggests that two redundant pathways operate in S or G 2 phase, respectively (24), whereas a recent study concludes that Cnp1 is replenished exclusively in G 2 phase (25). Overall, a common feature seen in various species is that CENP-A replenishment in many cases may occur without a tight junction with DNA replication (26).…”
mentioning
confidence: 99%